MANAGERIAL COMMUNICATION WITHIN PRE-UNIVERSITARY EDUCATION- MAIN COMPONENT OF THE EDUCATIONAL POLITICS - A CASE STUDY ON "MARIA TEIULEANU" ECONOMIC COLLEGE IN PITESTI - Iulia, MIELCESCU; Mădălina, STANCU; Lavinia, IANCU (Strategii Manageriale)
The present paper is structured in three parts. "Managerial communication and its strategies at organisational level" makes reference to Managerial Communication as a subject. The communication strategies at the organisational level are determined and some of them are also defined: control strategy, dynamic strategy, acceptance strategy, egalitarian strategy, structural strategy or avoidance strategy. The paper continues with "Communication within schools", on the example of "Maria Teiuleanu" Economic College in Pitesti, tackling the idea: "Valuable education- education for values". There follows the SWOT analysis of the activity within this institution. The managerial vision, the mission and the values promoted within the school are highlighted as well as some of the strategic priorities which will guide the whole activity, the didactic and educational activity for the current school year. The next perspectives which open in what regards the training of teachers within the field of education are tackled: 1. The development of some real collaboration relations between the experts who teach didactics and psycho pedagogy. 2. The training of some teachers who should be able to use the textbook in an optimum way under the conditions of the modern curriculum. 3. The reform of the promoting system on the grounds of the revision of the didactic personnel status and of the official introduction of some standards of didactic profession. The paper ends with some "Perspectives" which can improve communication within the school in the present situation and also within the existent institutions in what regards: A. Communication in the relations between school/teachers and students. B. Communication between the teachers, respectively teachers and the school managers. C. Communication between school and community (parents including). All things considered, it can be said that, according to the new requirements of the educational politics, the capable managers have the possibility and at the same time the duty towards themselves and the communities they manage, to establish the managerial strategy characterised by a set of values that they have to propose and promote within the learning and tuition process.